2003
DOI: 10.2337/diacare.26.6.1759
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Blood Glucose Monitoring Improves Glycemic Control in Stable, Insulin-Treated Veterans With Type 2 Diabetes

Abstract: OBJECTIVE -To examine the effect of intensified self-monitored blood glucose (SMBG) testing on glycemic control. RESEARCH DESIGN AND METHODS-Subjects with stable, insulin-treated type 2 diabetes performed SMBG using an electronic blood glucose meter before all meals and at bedtime for 8 weeks. Baseline data were collected on demographics, clinical characteristics, diet, and exercise. HbA 1c was measured at baseline, at 4 weeks, and at 8 weeks. After the intensified monitoring period, subjects resumed their usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 22 publications
5
73
0
3
Order By: Relevance
“…32 Like in type 1 diabetes, the rationale for the use of SMBG in insulin-treated type 2 diabetes is compelling and is supported by data from large prospective and observational trials. 30,33,34 Similar to the Diabetes Control and Complications Trial, the Kumamoto study showed that intensive insulin therapy guided by SMBG can reduce the risk of microvascular complications compared with conventional therapy in type 2 diabetes. 33 In the Diabetes Outcomes in Veterans Study (DOVES), intensified SMBG improved glycemic control (0.3% reduction in HbA1c over 1 year) in a large cohort of stable, insulin-treated veterans with type 2 diabetes.…”
Section: What Do the Guidelines Say On Smbg In Diabetes?mentioning
confidence: 98%
See 1 more Smart Citation
“…32 Like in type 1 diabetes, the rationale for the use of SMBG in insulin-treated type 2 diabetes is compelling and is supported by data from large prospective and observational trials. 30,33,34 Similar to the Diabetes Control and Complications Trial, the Kumamoto study showed that intensive insulin therapy guided by SMBG can reduce the risk of microvascular complications compared with conventional therapy in type 2 diabetes. 33 In the Diabetes Outcomes in Veterans Study (DOVES), intensified SMBG improved glycemic control (0.3% reduction in HbA1c over 1 year) in a large cohort of stable, insulin-treated veterans with type 2 diabetes.…”
Section: What Do the Guidelines Say On Smbg In Diabetes?mentioning
confidence: 98%
“…33 In the Diabetes Outcomes in Veterans Study (DOVES), intensified SMBG improved glycemic control (0.3% reduction in HbA1c over 1 year) in a large cohort of stable, insulin-treated veterans with type 2 diabetes. 34 Benefits were only seen in patients whose SMBG compliance exceeded 75% or those with baseline HbA1c > 8% (64 mmol/mol).…”
Section: What Do the Guidelines Say On Smbg In Diabetes?mentioning
confidence: 99%
“…While regular self-monitoring of blood glucose (SMBG) levels using glucometers is regarded as an essential tool for self-care [2,911], tests performed in accredited laboratories are preferred for confirming diagnoses, and are used in clinical and therapeutic decision making [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Since the price of the test strips decreased to almost one half compared to that in the year 2007 and there were also changes in the reimbursement of the strips from the public health insurance schemes (to a certain extent, the strips are also reimbursed to patients with less than three daily administrations of insulin), an increase in the frequency of blood glucose self-monitoring can be expected, which can have a positive effect on glycemic control in the groups of patients being monitored. [16][17][18] In addition to physiological and pathophysiological factors (higher body mass index, longer duration of diabetes, younger age, which are associated with higher HbA1c levels in patients with type 2 diabetes), 19 the internal factors influencing the glycemic control also include a group of factors that could be called skills and are related mainly to insulin therapy. These factors include, in particular, adherence to dietary recommendations and restrictions, conditions associated with hypoglycemic episodes (see later), the frequency and use of self-monitoring, adherence to insulin therapy, and sufficient physical activity.…”
Section: Glycemic Control (Hba1c)mentioning
confidence: 99%